Metode Pendidikan Dalam Mengenalkan Tuhan Kepada Anak - Fatah Hidayat; Faisal Faisal; Aida Imtihana (STIKes Ibnu Sina Ajibarang, 2023)
The question of God arises in children basically due to environmental influences. The image of God is often mixed with various experiences he gets, because in fact these experiences are useful for instilling impressions in the child's mind, including those seen and heard. Knowing God is something abstract. While the logic of children's thinking is concrete. In the logic of adult thinking, parents can feel that God is All-Seeing, God is All-Powerful and All-All. Everything in the universe belongs to God, and all will return to Him. Life in this world is only temporary, life in the afterlife will be eternal. The statement or explanation for a child will not be easy to understand and the logic is too complicated. Therefore, there is a need for a special approach and method of knowing God to children, in accordance with the development of the soul in children. In introducing God to children, parents need to set a good example, read religious stories, teach prayer, attend religious activities, give appropriate explanations, and create a supportive environment. With the right educational methods, children can understand and develop their relationship with God early on.